IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DAN DAMPAKNYA TERHADAP KINERJA GURU DI SDN DERMO II BANGIL - Rif'atul Khamdiyah; Taufiq Harris; Suyitno Suyitno (Jurnal Manajemen Pendidikan, 2026)
Academic supervision plays a strategic role in improving instructional quality, yet it is often perceived merely as an administrative activity. This study aims to analyze the implementation of academic supervision by the principal and its impact on teacher performance at SDN Dermo II Bangil. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using an interactive data analysis model. The findings reveal that academic supervision is implemented in a structured, reflective, and collaborative manner and functions as a mechanism for teacher professional development. Supervision positively influences lesson planning quality, instructional strategy variation, and formative assessment practices. It also enhances teacher motivation and professionalism, although its implementation is constrained by limited supervisory time and administrative workload. The study concludes that meaningful and contextual academic supervision contributes significantly to improving teacher performance and instructional quality in primary schools.